The Effect of Fracture Pattern of Anterior Teeth on Fracture Strength of Silorane- Based and Nanohybrid Composite Restorations - Sharafeddin F; Zareie A; Jowkar Z (Shiraz University of Medical Sciences, 2017)
Statement of problem: One of the most important concerns in choosing a treatment plan for a fractured anterior teeth is their fracture pattern. Selecting the best restorative material is crucial in restoration of them. Objective(s): The present study was aimed to evaluate the effects of fracture pattern and the composite type on the fracture strength of frac-tured anterior maxillary teeth. Materials and Methods: 40 sound maxillary anterior teeth were randomly divided into four groups of ten teeth (H1, H2, O1, and O2). In H1 and H2, the incisal edges were cut horizontally by 3mm below the incisal edge and in O1 and O2 the incisal edges were cut obliquely from the middle of incisal edge to 6mm below the incisal edge on the proximal side. A nanohybrid composite (Z350) was used for restoring the samples of H1 and O1 whilst a silorane-based composite (P90) was used in H2 and O2. Fracture strength was measured and the failure mode was recorded. Data were analyzed using one way analysis of variance (ANOVA) and Tamhane's post hoc tests. The level of significance was p ˂0.05. Results: Restoration with composite resin Z350 showed a higher strength in both cutting patterns (p <0.001). Fracture strength was greater in horizontal pattern, regardless of the composite type used for restoration; however, the difference was not statistically significant for P90 (p= 0.930). Conclusions: Fracture resistance of the fractured anterior teeth restored with Z350 is higher than that achieved with P90 for both fracture pat-terns.